Komunikasi Simbol Tradisional Jawa pada Ruang Pendopo di Restoran Warisan By Lordji - Lauw, Laura; Pandrianto, Nigar (Koneksi, 2024)
Each restaurant certainly has its own charm and characteristics, one of which is the Warisan By Lordji Restaurant. This restaurant has a unique concept, which is a restaurant with a traditional Javanese concept. This can be seen from the shape of the building, indoor and outdoor decorations, until the food menu. In the restaurant building with a traditional Javanese concept, of course it has certain spatial functions, symbols and meanings in communication. In this case, researcher will discuss how spatial functions as a medium for communicating traditional Javanese symbols at the Warisan By Lordji Restaurant. The method used in this research is a qualitative descriptive method. The theories used are intercultural communication, traditional architecture, spatial, symbols, pavilions as symbols, and store atmosphere. The results and conclusions that can be drawn from this research are that in today's modern world, most restaurants that use traditional Javanese concepts no longer have or contain sacred symbolic values. Most of the symbols on pavilions in restaurants have been negotiated or mixed and adapted to modern values. However, even though it has been mixed with modern values, restaurants with a traditional Javanese concept are still considered attractive and unique to this day.   Setiap restoran memiliki daya tarik dan ciri khas tersendiri, salah satunya Restoran Warisan By Lordji. Restoran ini memiliki konsep yang unik yaitu dibangun dengan konsep tradisional Jawa. Hal ini dapat dilihat dari bentuk bangunannya, dekorasi dalam ruangan maupun luar ruangan, hingga menu makanan. Bangunan restoran dengan konsep tradisional Jawa, memiliki fungsi ruang, simbol-simbol dan arti tertentu pada komunikasi. Penelitian ini mengenai bagaimana fungsi ruang sebagai media komunikasi simbol tradisional Jawa pada Restoran Warisan By Lordji. Metode yang digunakan dalam penelitian ini merupakan metode deskriptif kualitatif. Teori yang digunakan antara lain komunikasi antarbudaya, arsitektur tradisional, ruang (spatial), sampai simbol, pendopo, serta store atmoshphere. Kesimpulan yang dapat ditarik melalui penelitian ini antara lain di dunia modern sebagian besar restoran yang menggunakan konsep tradisional Jawa sudah tidak memiliki atau mengandung nilai-nilai simbolik yang bersifat sakral. Sebagian besar simbol pada pendopo di restoran sudah dinegosiasikan atau bercampur dan disesuaikan dengan nilai modern. Namun meskipun telah bercampur dengan nilai modern, restoran dengan konsep tradisional Jawa masih tetap dianggap menarik dan diaggap unik sampai saat ini.